Selling shares in cool - Gieve, Simon (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
In the context of globalisation of production of sports apparel and the plundering of semiotic cultural resources in the design of fashionable sportswear, this paper examines the language of the interpersonal elements of Company Annual Reports in the US sports/fashion industry, in particular the Letter to Shareholders in recent Annual Reports from Hilfiger, Nike, Polo Ralph Lauren and Reebok. In these Reports, financial reporting is increasingly being colonised by marketing discourse, and the flexible potential of the Annual Report genre is being exploited to represent companies to (potential) shareholders in a compound of the discourses of sports, business, and finance with those of globalisation, primacy, and Americanism. Globalisation for these companies is effectively presented as the outward expansion of American values into the world market.